1997
DOI: 10.1038/sj.gt.3300499
|View full text |Cite
|
Sign up to set email alerts
|

Efficient adenovirus-mediated gene transduction of normal and leukemic hematopoietic cells

Abstract: We evaluated the efficiency of adenovirus-mediated gene targeted cells. A novel protocol for the efficient transduction transfer into normal and malignant human hematopoietic of adenovirus into B-CLL cells was presented. We showed cells. An E-1 and E-3 deleted, replication-defective recomthat anti-CD40 mAb or CD40 ligand acts in synergy with binant Ad.RSV␤gal vector was used and the transduction rhIL-4 to enable the transduction of approximately 50-75% efficiency was studied at a multiplicity of infection of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 5 publications
4
29
0
1
Order By: Relevance
“…28 Only 40% of the total bone marrow, 15% of CD34 + stem cells, 9 and a small proportion of T 29 and B lymphocytes express CAR, while integrins are generally absent on hematopoietic cells and cell lines. Mitogens and IL2 induce expression of integrins 30 and CAR, respectively, on T cells, 29 while CD40 cross-linking 31 and IL4 stimulation 32 up-regulate integrins on B cells and allow them to be infected by adenovirus. Similarly, CD34 + cells appear to be more permissive to Ad5 infection after culture with various cocktails of cytokines including SCF, IL3, G-CSF, Flt3 ligand, Tpo, and c-Kit ligand.…”
Section: Discussionmentioning
confidence: 99%
“…28 Only 40% of the total bone marrow, 15% of CD34 + stem cells, 9 and a small proportion of T 29 and B lymphocytes express CAR, while integrins are generally absent on hematopoietic cells and cell lines. Mitogens and IL2 induce expression of integrins 30 and CAR, respectively, on T cells, 29 while CD40 cross-linking 31 and IL4 stimulation 32 up-regulate integrins on B cells and allow them to be infected by adenovirus. Similarly, CD34 + cells appear to be more permissive to Ad5 infection after culture with various cocktails of cytokines including SCF, IL3, G-CSF, Flt3 ligand, Tpo, and c-Kit ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Successful adenoviral transduction of CLL cells was achieved, but only when the virus was administered at a very high multiplicity of infection (MOI). [10][11][12][13] Adeno-associated viral vectors were used as an alternative, but appropriate prestimulation of the CLL cells by CD40 ligand (CD40L) expressing feeder cells or IgM crosslinking appeared to be necessary for transgene expression. [14][15][16] Viral gene transfer methods suffer from additional drawbacks: the production of vectors is laborious and time-consuming and needs specialized equipment, laboratory costs are elevated due to safety requirements, clinical applications are currently restricted and target cells need to express specific receptors to allow binding and entry of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…7,28,[43][44][45] These initial studies were discouraging for the low infectivity shown by the cells and fresh tissue tested. [43][44][45] In one study, high moi of adenoviral particles were necessary to infect cells derived from CLL.…”
Section: Adenovirus-mediated Gene Therapy For Lymphoproliferative Dismentioning
confidence: 99%
“…7,28,[43][44][45] These initial studies were discouraging for the low infectivity shown by the cells and fresh tissue tested. [43][44][45] In one study, high moi of adenoviral particles were necessary to infect cells derived from CLL. 28 In recent years, other investigators and we have shown that the expression of CAR that was detected by flow cytometry analysis of cells stained with monoclonal antibody anti-CAR, RmcB, varies among cells derived from several lymphoproliferative malignancies as compared with normal cell counterparts.…”
Section: Adenovirus-mediated Gene Therapy For Lymphoproliferative Dismentioning
confidence: 99%